The 9+ screening test score does not predict injuries in elite floorball players - Tervo, T.; Ermling, J.; Nordström, A.; Toss, F. (Scandinavian Journal of Medicine & Science in Sports, 2020)
We aimed to examine whether the 9+ screening test score could predict injuries in elite floorball players. Eighty-four elite floorball players participated in the study. At baseline, two physiotherapists assessed the participants using the 9+ screening test. The test score reflects strength, stability, mobility, and functional movement pattern with an emphasis on the lower body and core. Injuries that occurred the following season (2013/2014) were recorded by medical staff, coaches, and/or self-reported by the players. Overall, there was no relationship between the 9+ screening test score and injury risk (OR = 0.96 per SD lower test score, P = .84). We, therefore, conclude that the 9+ screening test is not suited for overall injury risk prediction in elite floorball players. Whether the test may be used to predict risk of certain injury types more strongly related to inadequate mobility and strength (eg, muscle ruptures or strains) warrants further investigation.